Theater in education as an innovative pedagogical tool - Kiprianos, Pandelis; Spyropoulou, Maria (Papanda Publisher, 2025)
With today's crisis of values, one of the main demands for ensuring democracy is the restoration of trust in people's relationships. It is considered more useful, however, to consolidate it from the first years of a person's life. It begs the question, therefore, how can trust be acquired at this stage of life. The arts, with their potential to increase the empathy of individuals, can be the basis for their development. By means of a quantitative methodological approach, the paper focuses on the art of theater and explores its role in education as an innovative pedagogical tool in building trust in primary education. The article examines the evolution of social relationships between children over time. While teachers cannot assess these relationships directly due to time constraints, these relationships do exist. Children have learned to accept the diversity of their classmates in the context of lessons, leading to shared experiences both inside and outside of school. Although not all social relations are successful, the educational process has contributed to the strengthening of respect for others between them which can positively affect the reduction of marginalization.